Management of Genu Sinistra Osteoarthritis (Oa) With Ultrasound (Us) Modality, Transcutaneous Electrical Nerve Stimulation (Tens) And Strengthening Exercise - Noviyanti Dwiputri; Heri Purnama Pribadi (Indonesian Vocational Research Journal, 2021)
Osteoarthritis (OA) is a degenerative disease characterized by the degradation of cartilage (cartilage) which causes bones to rub against each other, causing joint stiffness and pain. One of thephysiotherapy treatments that can reduce pain and increase joint range of motion is electrotherapy and strengthening exercise modalities. The purpose of this case study is to determine the effect ofelectrotherapy modalities such as ultrasound (US), transcutaneous electrical nerve stimulation (TENS) and strengthening exercise on reducing pain and increasing the range of motion of the knee joint incases of knee osteoarthritis. This case study was conducted at RSUD Ibnu Sina Gresik, for 2 months. The results of the case study show that the combination of US, TENS and strengthening exercise can reducepain, resulting in an increase in ROM. Measurement of pain and ROM values using the NRS scale. The results of the initial measurements showed the value of silent pain was 2, the value of tenderness was4, and the value of motion pain was 5 decreased to a silent pain value of 0, the value of tenderness was 2 and the value of motion pain was 2. Meanwhile, ROM showed an increase in initial ROM of treatmentfrom 110° to 125. °. The conclusion of this case study shows that the administration of US, TENS, and strengthening exercise in the case of osteoarthritis of the left knee can reduce the degree of pain andincrease the joint range of motion in the patient's left knee